Allergenity Test of Porang Bulb Variant (Amorphophallus oncophyllus Hook.) By ELISA Ig-E Method - Sofy Permana; Sri Widyarti; Serafinah Indriyani; Dian Siswanto; Aris Soewondo (Natural B, Journal of Health and Environmental Sciences, 2012)
Porang (Amorphophalus oncophyllus Hook.), a tuber plant, is intensively explored for export commodities from East Java and as a raw food stuff material for domestic industry. The prospects of Porang tubers as the healthy food is interesting, however some studies are needed for their allergy effects. It was thought that the allergy effects of Porang are caused by the composition of Calcium Oxalate crystal that leads the itching and irritation in the mouth. On the other hands, the food allergy is usually caused by unchanged protein during food digesting. Some proteins have been known that play a role in Calcium Oxalate crystal (Matrix proteins) formation, they are: Asp-rich and Ser-rich acidic proteins that are tightly bound to Calcium. So, substantially the allergen of Porang tuber is from the matrix protein, not from its crystal. The allergen in the food is usually a protein that is not change during the food digestion. In this study, it has been done the allergic test of some Porang tuber variants, namely: Sumber Baru-Jember; Klangon, Saradan-Madiun and Sumber Bendo, Saradan-Madiun, by ELISA-IgE from rat’s blood serum that have been orally treated by raw Porang tubers powder before. The SDS-PAGE analysis shows that the proteins bands profiles are similar between raw and steamed Porang tubers (appearance Molecular Weight: 18 and 15 kDa). But, those raw Porang tubers bands are thicker than the steamed ones. The thickness of those raw Porang tubers decrease from 25 to 50 %, compare to those steamed ones. It means that the steaming of Porang is effective to decrease the potential allergy of Porang for consumptions. The allergic test analysis by ELISA-IgE revealed that the potential allergy of Porang are: Sumber Baru (Jember) > Porang var. Klangon - Saradan (Madiun) > Porang var. Sumber Bendo - Saradan (Madiun), respectively.